KAJIAN HIDROLIS RUNTUHNYA EMBUNG JOHO DI KECAMATAN SEMEN KABUPATEN KEDIRI - Suhudi Suhudi (Universitas Tribhuwana Tunggadewi, 2008)
Dam Joho located in Kedak river with especial function as is ready standard water to resident in three villages. Execution of project of Dam Joho planned 210 calendar days at dry season, expected is final of December 2006 can finish. At mid of December happened rain with high intensity causing admission filling of water in accumulating basin sudden and happened by a problem of that is collapsing of Dam Joho. This Research aim to evaluate to collapse him of Dam Joho by comparing analysis charge floods of planning early and analysis charge floods pursuant to rainfall during 20 the last year. Besides, knowing stability storey; level of dam the at the of happened problem. Pursuant to information of executor contractor that face elevation irrigate moment happened to collapse him of Dam Joho is 510,30 m. Comparison of inflow discharge and outflow discharge can be obtained by interpolation, so that charge inflow obtained by 1,2249 multiplied with outflow discharge 139,603 m3/s, its result 171,003 m3/s at time period 193 year. Safety factor stability number of dam to stream of seepage and to slide evaluated in a condition face irrigate full in part of upstream of dam, exceeding from which is permitted so that happened to collapse him of Dam Joho